Transition of clinical biomarker status from childhood into adolescence-A prospective study in children from eight European countries. - Anna Floegel; Paola Russo; Toomas Veidebaum; Michael Tornaritis; Dénes Molnár; Lauren Lissner; Stefaan De Henauw; Luis A Moreno; Wolfgang Ahrens; Manuela Marron; Claudia Börnhorst (PLoS ONE)
Purpose Understanding factors influencing clinical biomarkers is important for the prevention of chronic disease. This study aimed to estimate transitions of biomarker status from childhood to adolescence and to identify determinants of biomarker status in early life in a prospective children cohort. Subjects and methods Our sample comprised 1295 children participating in the baseline (2007/08) and second follow-up examination (2013/14) of the multi-center IDEFICS (Identification and prevention of Dietary- and lifestyle-induced health EFfects In Children and infantS)/I.Family study. Clinical blood biomarkers including glycated hemoglobin A1c (HbA1c), high-density lipoprotein cholesterol (HDL-cholesterol), triglycerides, C-reactive protein (CRP), interleukin 6, ferritin, leptin and insulin-like growth factor 1 (IGF-1) were repeatedly measured in 2007/2008 (age range: 3.0 to <10.0 years) and in 2013/2014. Latent transition analysis was used to estimate biomarker statuses and transition probabilities; determinants of biomarker status were estimated using mixed-effects models. Results Four distinct biomarker statuses were identified: (1) "normal" (all biomarkers low/medium; except HDL-cholesterol; reference), (2) "low leptin/IGF-1/HbA1c", (3) "dyslipidemia/high leptin" and (4) "inflammation". Children classified as "low leptin/IGF-1/HbA1c" at baseline were most likely to stay in this status (89.8%) or to change to the "normal" status (10%) during follow-up. Compared to "normal" children, children classified as "low leptin/IGF-1/HbA1c" were less likely to have a family history of diabetes (0.26 [0.08;0.86]; odds ratio (OR) and 95% confidence interval) or hypertension (0.53 [0.29;0.99]) and the children (0.32 [0.27;0.38]) as well as their mothers (0.93 [0.88;0.98]) had a lower BMI. Children from families with low/medium education had a 55% [9%-119%] higher risk of being in the "dyslipidemia/high leptin" and 49% [1%-121%] higher risk of being in the "inflammation" status as compared to children in the "normal" status. Membership in a sports club reduced the latter risks by 28% [2%-47%] and 40% [17%-56%], respectively. Conclusions European children showed distinct phenotypes for the investigated biomarkers. Especially parental characteristics like a family history of diabetes or hypertension, a high maternal BMI, or low/medium education were associated with unfavorable biomarker status in children.